Senescence and Senescence-Related Disorders - Wang, Zhiwei; Inuzuka, Hiroyuki (IntechOpen, 2013)
Senescence is a biological process that causes a progressive deterioration of structure and function of all organs chronologically. Recent studies have revealed the detailed molecular mechanisms of senescence using cell culture system and experimental organisms. It is thought that senescence is a potential cause for the development of various age-related disorders such as cancer, cardiovascular and neurodegenerative disorders. This book discusses in detail senescence and its related diseases by distinguished researchers and practicing clinicians. The cumulative knowledge from the studies could lead to developing new approaches for anti-senescence interventions.